2011
DOI: 10.1073/pnas.1005494108
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural signatures of threat learning in adolescents and adults

Abstract: Most teenage fears subside with age, a change that may reflect brain maturation in the service of refined fear learning. Whereas adults clearly demarcate safe situations from real dangers, attenuating fear to the former but not the latter, adolescents' immaturity in prefrontal cortex function may limit their ability to form clear-cut threat categories, allowing pervasive fears to manifest. Here we developed a discrimination learning paradigm that assesses the ability to categorize threat from safety cues to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
177
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 48 publications
(62 reference statements)
15
177
2
1
Order By: Relevance
“…The finding that adolescents showed stronger conditioning relative to adults on the latency of first fixation to the CSþ measure is consistent with previous studies reporting elevated threat responding during adolescence (Den & Richardson, 2013;Lau et al, 2011). Specifically, in the present study, adolescents showed a decrease in the latency of first fixation to the CSþ from preacquisition to conditioning.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The finding that adolescents showed stronger conditioning relative to adults on the latency of first fixation to the CSþ measure is consistent with previous studies reporting elevated threat responding during adolescence (Den & Richardson, 2013;Lau et al, 2011). Specifically, in the present study, adolescents showed a decrease in the latency of first fixation to the CSþ from preacquisition to conditioning.…”
Section: Discussionsupporting
confidence: 94%
“…Although there were no differences in fear ratings of the CSþ (i.e., the threat cue that actually predicted the aversive US) between the two age groups, adolescents had higher fear ratings to the CSÀ (i.e., the safety cue that did not predict the aversive US) than did the adults. Lau et al (2011) concluded that overgeneralization of fear from the CSþ to the CSÀ in adolescents was driven by greater subcortical relative to cortical activity, providing support for the "imbalance" model.…”
Section: Introductionmentioning
confidence: 95%
“…Children as young as 3 years show evidence of fear acquisition (Gao et al, 2010), with discrimination between an aversively conditioned and a neutral stimulus (CS þ 4CS À ) improving with age (Gao et al, 2010;Glenn et al, 2012). This increased discrimination ability with age continues into adulthood, and is associated with distinct developmental patterns of neural activity during fear learning (Lau et al, 2011). Consistent developmental changes in fear extinction learning have been observed across species.…”
Section: Developmental Changes In Fear-learning Circuitssupporting
confidence: 48%
“…Similar to findings in anxious adults (e.g., Michael, Blechert, Vriends, Margraf, & Wilhelm, 2007;Orr et al, 2000;Peri, Ben-Shakhar, Orr, & Shalev, 2000), experimental studies have found that anxious, relative to nonanxious, youth show larger physiological responses particularly during initial trials of extinction, and more negative evaluations of the CS+ than the CSÀ, as well as larger responses overall to both CSs (e.g., Craske et al, 2008;Jovanovic et al, 2014;Lau et al, 2008Lau et al, , 2011Liberman, Lipp, Spence, & March, 2006;Waters, Henry, & Neumann, 2009). If CBT reduces fear via extinction principles during exposure therapy (Vervliet et al, 2013), then individual differences during extinction trials may predict response to CBT.…”
Section: Introductionmentioning
confidence: 79%